Risks of distribution of potato viruses in agrocensors of Ukraine - Dmitruk, O.; Derevyanko, S.; Reshotko, L. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2018)
As a result of the conducted monitoring studies, the spread of viral diseases of potatoes in Ukrainian agrocentoses, which poses a potential threat to the cultivation of this crop. In the nurseries of elite seed potatoes, the risks of spreading M-, S-, Y-viruses of potatoes, both in monoinfection and in the pathocomplexes are determined. It has been established that in the crops the entomophilic M-virus is prevalent in monoinfection (43.5%) or in combination with other mosaic viruses. In agrocentoses with potatoes, S — potato virus — 7.2%; YVP — 2.8% and in the patokompleksa SVP + YVP — 2.8% of the examined varieties. In most tested varieties, the Y-virus appears as a component of various complex infections with mosaic symptoms (25%), which is a feature of the Y-viral present at the present time. In modern conditions, there is a need for phyto-viral monitoring of agrocenoses, obtaining basic data for the development of measures to increase potato productivity by improving the phytosanitary state of agroecosystems and seeding on a non-virus basis.